Nieefektywność systemów wyborczych w postkomunistycznej Rumunii. Ujęcie przedmiotowe - Tomuleț, Cristina (Studia Wyborcze, 2020)
In this article, I analyze the ineffectiveness of electoral systems in post-communist Romania using a substantive approach. To this end, I firstly maintain that an effective electoral choice, conducive to actual representativity, is characterized by the following qualities and guarantees: 1)the electorate should have a range of options; 2) the options in question should be viable;3)the persons elected should be willing to implement the will of the electorate; 4) the electedpersons should be held accountable, in one way or another, if they blatantly and systematicallyrefuse to implement the will of the electorate. I then argue that neither of the previously mentioned qualities and guarantees that characterize an effective electoral choice in democratic systems exists in the case of Romania, largely due to its post-communist legacy.